Does Lack of EWSR1-ATF1 Fusion Exclude Diagnosis of Salivary Gland Clear Cell Carcinoma? - Sibel Sensu; Nusret Erdogan; Kayhan Basak; Egzona Qipa; Murat Buyukdogan (National Cancer Center - Dharmais Cancer Hospital, 2021)
Introduction: Ewing sarcoma breakpoint region 1- activating transcription factor 1 (EWSR1-ATF1) fusion is mentioned as a diagnostic marker in favor of clear cell carcinoma in the differential diagnosis of clear cell neoplasms of salivary glands. However, in literature, its positivity is reported between 82% and 93%. In salivary glands, various benign and malignant primary tumors, as well as odontogenic neoplasms and metastatic cases, present with a varied number of clear cells. Clear cell carcinoma of the salivary gland is a rare entity with distinct histochemistry and immunohistochemistry features.Case Presentation: We present a clear cell carcinoma of the salivary gland showing cytoplasmic Periodic acid–Schiff (PAS) (+), mucin (-) staining, cytokeratin (CK), CK7, and P63 immunoreactivity without EWSR1-ATF1 fusion. Conclusions: We conclude that clinical, morphological, and immunohistochemical analyses should be the guide for diagnosis even though molecular analysis does not support it.